Reconstruction of a nonlinear heat transfer law from uncomplete boundary data by means of infrared thermography. (7th October 2016) - Clarelli, Fabrizio; Inglese, Gabriele
Abstract: Heat exchange between a conducting plate and the environment is described here by means of an unknown nonlinear function F of the temperature u . In this paper we construct a method for recovering F by means of polynomial expansion, perturbation theory and the toolbox of thermal inverse problems. We test our method on two examples: In the first one, we heat the plate (initially at 20 ° C ) from one side, read the temperature on the same side and identify the heat exchange law on the opposite side (active thermography); in the second example we measure the temperature of one side of the plate (initially at 1500 ° C ) and study the heat exchange while cooling (passive thermography).